Synthesis, characterisation and corrosion inhibition screening of Co(Ii) dithiocarbamate complexes in HCl and H2SO4 / Mimi Wahidah Mohd Radzi ... [et al.] - Mohd Radzi, Mimi Wahidah; Alias, Nur Alia Atiqah; Esa, Fasihah; Dzulkifli, Nur Nadia (Universiti Teknologi MARA, Negeri Sembilan, 2021)
Most industries use acids during cleaning processes where they may cause severe corrosion attacks on metal surfaces. This study utilised a corrosion inhibitor to reduce the corrosion rate. Cobalt(II) N-methylcyclohexylamine dithiocarbamate, Co[MeCycHexdtc]2 and cobalt(II) N-ethylcyclohexylamine dithiocarbamate, Co[EtCycHexdtc]2 were synthesised by using the in-situ method with a molar ratio of 2:2:1 (carbon disulphide:amine:metal salt) in cold ethanolic solution and characterised by using the Fourier Transform Infrared-Attenuated Total Reflectance (FTIR-ATR) and Ultraviolet-Visible (UV-Vis) spectroscopies. In the FTIR-ATR analysis, the presence of dithiocarbamate moiety was proven by the data shown with the presence of a new specific stretching bands, thioureide band, υ(CN) which is found in the range of 1478–1481 cm-1 and υ(CS) in 1010-1012 cm-1 of the spectra in both Co(II) complexes. For UV-Vis analysis, the Co(II) complexes showed two transitions, π→π* and n→π* transitions, which indicated that the coordination between metal ions and dithiocarbamates ligands has successfully formed. The presence of peaks above 400 nm confirmed the d-d transition of Co(II) complexes. Furthermore, mild steel corrosion inhibition screening was studied using two corrosive media (1 M HCl and 1 M H2SO4) with and without varied inhibitor concentrations. As the inhibitor concentration increased, the efficiency of the corrosion inhibitor also increased at a constant temperature.